2003
DOI: 10.1007/s00412-003-0253-5
|View full text |Cite
|
Sign up to set email alerts
|

The ThioredoxinT and deadhead gene pair encode testis- and ovary-specific thioredoxins in Drosophila melanogaster

Abstract: So far, two thioredoxin proteins, DHD and Trx-2, have been biochemically characterized in Drosophila melanogaster. Here, with the cloning and characterization of TrxT we describe an additional thioredoxin with testis-specific expression. TrxT and dhd are arranged as a gene pair, transcribed in opposite directions and sharing a 471 bp regulatory region. We show that this regulatory region is sufficient for correct expression of the two genes. This gene pair makes a good model for unraveling how closely spaced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 48 publications
2
52
0
Order By: Relevance
“…The primer pair 5Ј-CCACCATCTGCGACATA-AACAG-3Ј and 5Ј-CGACGAGTAATTTGGTACACTG-3Ј will amplify only the endogenous Pof transcript, 5Ј-CCACC-ATCTGCGACATAAACAG-3Ј and 5Ј-CGTCGCCGTCCA-GCTCGACCA-3Ј only the Pof.EYFP transcript, and 5Ј-AAA-GACGATGCCAAGGACTCAC-3Ј and 5Ј-GCTTGGCGGCC-GTGCCGACA-3Ј will amplify the neighboring gene CG4806. Poly(A) ϩ RNA was isolated as described (28). One microliter of poly(A) ϩ RNA, pd(T) [12][13][14][15][16][17][18] first-strand primer, primer pairs indicated above, and Ready-to-Go RT-PCR beads (Amersham Biosciences, Piscataway, NJ) was used in each RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The primer pair 5Ј-CCACCATCTGCGACATA-AACAG-3Ј and 5Ј-CGACGAGTAATTTGGTACACTG-3Ј will amplify only the endogenous Pof transcript, 5Ј-CCACC-ATCTGCGACATAAACAG-3Ј and 5Ј-CGTCGCCGTCCA-GCTCGACCA-3Ј only the Pof.EYFP transcript, and 5Ј-AAA-GACGATGCCAAGGACTCAC-3Ј and 5Ј-GCTTGGCGGCC-GTGCCGACA-3Ј will amplify the neighboring gene CG4806. Poly(A) ϩ RNA was isolated as described (28). One microliter of poly(A) ϩ RNA, pd(T) [12][13][14][15][16][17][18] first-strand primer, primer pairs indicated above, and Ready-to-Go RT-PCR beads (Amersham Biosciences, Piscataway, NJ) was used in each RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The microarray analysis indicated that transcripts of TrxT, a testis specific isoform of thioredoxin (Svensson et al, 2003), (Fig. 7F).…”
Section: Differential Requirements For Topi and Achi/vis For Expressimentioning
confidence: 99%
“…Another feature these genes have in common is that they are members of clusters of related genes, with different expression patterns. TrxT is found adjacent in the Development 131 (8) Research article genome to the female specific thioredoxin, deadhead (Svensson et al, 2003). CG8349 is the 3′-most of a cluster of three predicted cytidine deaminase genes (the others being CG8360 and CG8353).…”
Section: Structure Of Target Promotersmentioning
confidence: 99%
“…In Drosophila, out of 11 predicted Trxs, 3 classical Trx genes have been identified (deadhead [dhd], Trx-2, and TrxT), and mutants for all 3 have been characterized. The dhd and trxT genes form a cluster on the X-chromosome, and both appear to be germ-line specific, dhd being associated with the nurse cell nuclei and karyosomes of the ovary, and trxT with the spermatocytes (111). While Trx-2 has been colocalized with Trx-T, it is also expressed at significant levels in somatic tissues, and thus represents an attractive target for the evaluation of longevity effects.…”
Section: Thioredoxinsmentioning
confidence: 99%